2021
DOI: 10.28991/esj-2021-01262
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Management Energy System and Control Strategies for Isolated Hybrid Solar-Wind-Battery-Diesel Power System

Abstract: This paper proposes optimal control strategies of a standalone Hybrid Power System (HPS) to supply sustainable and optimal energy to an isolated site with improved quality of electrical energy. A topology of Isolated Hybrid Power System (IHPS) is proposed, consists of: a Photovoltaic System (PVS), a Wind Energy Conversion System (WECS), electronic power devices controlled to maximize energy production from renewable sources and to maintain the constant DC-link voltage, a Battery Energy Storage System (BESS), D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…For instance, some literatures do not include waste and transport as such, but only energy from the perspective of renewable resources and carbon emissions (Qerimi et al, 2020). Similarly, there are literatures on energy management systems in various contexts, for example, optimisation even via hybridising renewable and non-renewable energy resources such as solar, wind, batteries and diesel (Tahiri et al, 2021) while waste and transport are not included at all. Also, there are literatures which would focus only on the waste element of the nexus and the other two are totally excluded.…”
Section: Waste-energy-transport (Wet) Nexusmentioning
confidence: 99%
“…For instance, some literatures do not include waste and transport as such, but only energy from the perspective of renewable resources and carbon emissions (Qerimi et al, 2020). Similarly, there are literatures on energy management systems in various contexts, for example, optimisation even via hybridising renewable and non-renewable energy resources such as solar, wind, batteries and diesel (Tahiri et al, 2021) while waste and transport are not included at all. Also, there are literatures which would focus only on the waste element of the nexus and the other two are totally excluded.…”
Section: Waste-energy-transport (Wet) Nexusmentioning
confidence: 99%
“…In this vein, many researchers intensified their work to design optimal control strategies for a standalone hybrid power system (HPS). For example, Tahiri et al (2021) propose a complex tool ranging from photovoltaic system (PVS) and wind energy conversion system (WECS) to a pulse width modulation (PWM) voltage source inverter (VSI). Unlike them, Qerimi et al (2021) develop a system able to replace conventional water heaters with domestic solar water heaters (DSWH).…”
Section: Literaturementioning
confidence: 99%
“…Responses (%) These results showed that Chinese regulators are very concerned about the secondary effects of the remediation process, and they had little incentive to deal with the elements of the policy that did not require much enforcement. Greenhouse gas (GHG) emissions and energy-saving have always been hot topics in various fields [46], but the degree of adoption for these factors was low and was not thought to be strengthened. This situation is similar to some previous studies, mainly focusing on the researchers [28][29][30]47].…”
Section: Environmental Dimensionmentioning
confidence: 99%